2010
DOI: 10.2337/db10-0328
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, Defective Insulin-Mediated Fatty Acid Suppression, and Coronary Artery Calcification in Subjects With and Without Type 1 Diabetes

Abstract: OBJECTIVETo assess insulin action on peripheral glucose utilization and nonesterified fatty acid (NEFA) suppression as a predictor of coronary artery calcification (CAC) in patients with type 1 diabetes and nondiabetic controls.RESEARCH DESIGN AND METHODSInsulin action was measured by a three-stage hyperinsulinemic-euglycemic clamp (4, 8, and 40 mU/m2/min) in 87 subjects from the Coronary Artery Calcification in Type 1 Diabetes cohort (40 diabetic, 47 nondiabetic; mean age 45 ± 8 years; 55% female).RESULTSPeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
192
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(205 citation statements)
references
References 47 publications
7
192
2
4
Order By: Relevance
“…Measurement of insulin resistance is challenging in patients receiving insulin. Research studies have used regression equations derived from clamp studies; the derived estimated glucose disposal rate 157 predicts both CVD and diabetic nephropathy. 158,159 Subsequent observations from the EURODIAB Study also suggested that insulin resistance-related risk factors predicted CHD events in patients with T1DM, 138 and insulin resistance explains some portion of lipid abnormalities in young patients with T1DM.…”
Section: Obesity and Insulin Resistancementioning
confidence: 99%
“…Measurement of insulin resistance is challenging in patients receiving insulin. Research studies have used regression equations derived from clamp studies; the derived estimated glucose disposal rate 157 predicts both CVD and diabetic nephropathy. 158,159 Subsequent observations from the EURODIAB Study also suggested that insulin resistance-related risk factors predicted CHD events in patients with T1DM, 138 and insulin resistance explains some portion of lipid abnormalities in young patients with T1DM.…”
Section: Obesity and Insulin Resistancementioning
confidence: 99%
“…Different factors associated with impaired renal function are believed to contribute to adverse outcomes of patients with ACS. These factors include insulin resistance [4,5], oxidative stress [6], inflammation [7], endothelial dysfunction [8], vascular calcifications [9], and hypercoagulability [10]. Furthermore, the presence of chronic kidney disease is associated with a higher prevalence of baseline cardiovascular comorbidities including diabetes, heart failure, previous myocardial infarction, and stroke [1,2,11].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of IR in T1DM is likely due to a combination of supraphysiologic levels of exogenous insulin and obesity. In the past, it was thought that IR in T1D was primarily related to hyperglycemia (16), however, it was recently proposed that adults with T1DM have both impaired glucose utilization and impaired insulin-induced non-esterified fatty acid suppression, independent of glycemic control (17). Skeletal muscle IR is a known feature of T1DM and is due to decreased glucose transport into myocytes from impaired insulin-stimulated upregulation of GLUT4 mRNA (18).…”
Section: Introductionmentioning
confidence: 99%